2019
DOI: 10.1097/pcc.0000000000001847
|View full text |Cite
|
Sign up to set email alerts
|

Catecholaminergic Polymorphic Ventricular Tachycardia: The Cardiac Arrest Where Epinephrine Is Contraindicated*

Abstract: Objectives: To raise awareness among pediatric intensive care specialists of catecholaminergic polymorphic ventricular tachycardia; an uncommon cause of polymorphic ventricular tachycardia and ventricular fibrillation arrest in children and young adults where epinephrine (adrenaline), even when given according to international protocols, can be counter-productive and life-threatening. We review three cases of cardiac arrest in children, later proven to be catecholaminergic polymorphic ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Furthermore, the same study also reported in nine patients who had positive respond to adrenaline or epinephrine challenge test after inducing VT. Similarly in a case series reported by Bellamy et al , they also demonstrated in three different patients (age range, 4–10 years old), a positive response to epinephrine challenge test by inducing arrythmias in patients with RYR2 gene mutation, which successfully reverted by nadolol and flecainide ( 43 ).…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, the same study also reported in nine patients who had positive respond to adrenaline or epinephrine challenge test after inducing VT. Similarly in a case series reported by Bellamy et al , they also demonstrated in three different patients (age range, 4–10 years old), a positive response to epinephrine challenge test by inducing arrythmias in patients with RYR2 gene mutation, which successfully reverted by nadolol and flecainide ( 43 ).…”
Section: Discussionsupporting
confidence: 56%
“…In the differential diagnosis of sudden cardiac arrest without structural heart abnormalities, CPVT should always be considered along with similar conditions such as long QT syndrome, Brugada syndrome, and early repolarization syndrome [ 8 ]. Clinicians should hold a high index of suspicion for CPVT if the following features are exhibited: (i) cardiac arrest occurred during strong emotion or exercise; (ii) patient was previously healthy; (iii) EKG is normal at rest; (iv) adrenergic stimulation induces ventricular ectopy; and (v) ectopic beats become less frequent with anesthesia and opiates.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians should hold a high index of suspicion for CPVT if the following features are exhibited: (i) cardiac arrest occurred during strong emotion or exercise; (ii) patient was previously healthy; (iii) EKG is normal at rest; (iv) adrenergic stimulation induces ventricular ectopy; and (v) ectopic beats become less frequent with anesthesia and opiates. Furthermore, the finding of bidirectional ventricular tachycardia is pathognomonic for CPVT [ 8 ]. The clinical diagnosis of CPVT is dependent on stress-induced symptoms, family history, catecholamine infusion, and exercise stress testing.…”
Section: Discussionmentioning
confidence: 99%
“…Beta-blockers remain the first line of therapy, and epinephrine should be avoided, including in the setting of cardiac arrest/resuscitation. 174 …”
Section: Acute Managementmentioning
confidence: 99%